Alternativas nutricionales en cerdos, en etapa de crecimiento, para disminuir los costos de producción - Aranda Baños, Fabricio Miguel (2019)
The swine production in Ecuador is a little technified activity, however, the climatic conditions of our country allow to obtain a swine production according to the conditions of the environment in which they are developed, with available resources that allow obtaining a great variety of nutritional alternatives, both protein as energy, for the feeding of pigs in growth stage. Among the alternatives that exist are the use of crops with high biomass production and renewable energy as a measure of food that substitute protein sources and the use of food waste materials such as organic waste recycling, all in order to reduce costs of production. The purpose of this document is to improve knowledge about the different nutritional alternatives in pigs, in the growth stage, to reduce production costs and to obtain greater economic benefit to optimize the economic income of small and medium producers as livelihoods. For him and his family. As conclusions it was determined that good nutrition in pigs allows to obtain better productive parameters such as weight gain, feed conversion and yield with low production costs which allows to obtain greater economic benefit in the producers; Foods produced and processed by man originate several by-products and residues that can be destined for pig feeding, which must be analyzed so that they are correctly combined with other foods and form a balanced diet and the most important foods for Pig nutrition is sugarcane, tubers, banana roots, green plantain, rice by-products, wheat, fishing waste, milk by-products, fish meal, meat meal and soy flour